Women and health : today's evidence tomorrow's agenda. - World Health Organization (Geneva : World Organization, 2009)
Despite considerable progress in the past decades, societies continue to fail to meet the health care needs of women at key moments of their lives, particularly in their adolescent years and in older age. These are the key findings of the WHO report Women and health: today's evidence tomorrow's agenda. WHO calls for action both within the health sector and beyond to improve the health and lives of girls and women around the world, from birth to older age. The report provides the latest and most comprehensive evidence available to date on women's specific needs and health challenges over their entire life-course. The report includes the latest global and regional figures on the health and leading causes of death in women from birth, through childhood, adolescence and adulthood, to older age.--Publisher's description.
Understanding women's health in the world today -- The girl child -- Adolescent girls -- Adult women : the reproductive years -- Adult women -- Older women -- Policy implications -- Conclusion.
BIBINDX
Also available online.
Keywords: Women's Health; Global Health; Health Status Indicators; Life Change Events; Public policy; Women's Health Services -- trends; Statistics